Sustainable Approaches to the New Trinity Framework in Emerging Market Monetary Policy - Dudi Duta Akbar; Hermanto Siregar; Iman Sugema; Lukytawati Anggraeni (Jurnal Economia, 2026)
This study intended to explore the effect of financial literacy, social media use, and pay-later promotion on online impulsive and compulsive buying among youth. Using partial least squares structural equation modelling (PLS-SEM), 366 valid responses were analysed. Additionally, a moderation analysis using multigroup analysis (MGA) was conducted to determine if there are gender differences in these relationships. The finding revealed that of the three predictors of impulsive buying, only social media use had a positive and significant impact, while impulsive buying became a crucial determinant for compulsive buying. Interestingly, this study found that gender did not moderate the relationships outlined in the proposed model, indicating that the effects were similar for both males and females. This study suggests that youth should be wise in using social media, as it could lead to excessive purchasing that worsens the financial and psychological condition of both males and females.